Perbandingan Perlakuan Akuntansi Aset Biologis Berdasarkan PSAK 16 dan PSAK 69 Pada Perusahaan Agrikultur - I Gusti Ketut Agung Ulupui; Argie Destri Rahmani; Dwi Handarini; Hafifah Nasution (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2021)
This study aims to provide an overview of the differences in the accounting treatment of biological assets before and after the implementation of PSAK 69, namely based on PSAK 16 and PSAK 69. This study analyzed the implementation of PSAK 69 in agricultural companies listed on the Indonesia Stock Exchange in 2017-2018. The data analysis technique used in this study is an interactive model analysis technique namely to know the difference in accounting treatment for biological assets based on PSAK 16 and PSAK 69 in 15 agricultural companies. The are three aspects in compared; first on the recognition aspect, based on PSAK 16, agricultural companies recognize plantation crops as assets and do not recognize agricultural products as biological assets. Meanwhile, PSAK 69 measures the biological assets of agricultural companies using fair value less costs to sell and biological assets are not depreciated. Based on PSAK 16, agricultural companies disclose matters related to depreciation.Meanwhile, based on PSAK 69, agricultural companies disclose descriptions of biological asset groups and the value of gain/ losses arising from the use of fair value. Based on the results of the analysis 3 of 15 agricultural companies listed on the Indonesia Stock Exchange in the period 2018 has implemented PSAK 69 as much as 100%, the rest apply PSAK 69 as much as 50% to 94%.